Decolonizing research with Black youths - Salami, Bukola (Nursing philosophy, 2023)
Black youths experience poor mental health especially due to anti-Black racism. Research related to Black youths have been conducted on Black youths with little or no participation or engagement rather than with Black youths. This paper presents information from a dialogue on decolonizing nursing research. I draw on interviews and conversation cafes with around 120 Black youths in Canada to identify strategies for decolonizing research with Black youths. First, I reflect on my relations with the Indigenous land in which the study was conducted as well as my positionality as a Black woman. In this paper, I discuss how community based participatory action research can integrate capacity building component, amplify youth's voices and capitalize on the agency of youths as fruitful actors. I also reflect on the opportunities and benefits of decolonizing nursing research.